2008
DOI: 10.2108/zsj.25.614
|View full text |Cite
|
Sign up to set email alerts
|

Application of RNAi Technology to the Inhibition of Zebrafish GtHα, FSHβ, and LHβ Expression and to Functional Analyses

Abstract: Zebrafish (Danio rerio) were used as a model fish, and the technique of RNA interference (RNAi) was employed to knockdown three subunits of the gonadotropin alpha (GtHalpha, common alpha), follicle-stimulating hormone beta (FSHbeta), and luteinizing hormone beta (LHbeta) genes. Three short-hairpin RNA (shRNA) expression vectors and three mismatched shRNA expression vectors as controls for each subunit gene were constructed, and the depression efficiency was tested in vivo by microinjection; the RNA or protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The abnormal phenotypes were likely caused by the lack of Fsh production, because there was a strong correlation between the expression of fshb and the development of these phenotypes in fshb-MO fish. In agreement with our results, a recent study in the zebrafish showed that knockdown of cga (the common a subunit of Fsh, Lh, and Tsh) expression by RNA interference (RNAi) or morpholino also caused severe developmental defects in the embryos, including truncated tail and enlarged heart [41].…”
Section: Temporal Expression Of Gonadotropins In Zebrafishsupporting
confidence: 93%
“…The abnormal phenotypes were likely caused by the lack of Fsh production, because there was a strong correlation between the expression of fshb and the development of these phenotypes in fshb-MO fish. In agreement with our results, a recent study in the zebrafish showed that knockdown of cga (the common a subunit of Fsh, Lh, and Tsh) expression by RNA interference (RNAi) or morpholino also caused severe developmental defects in the embryos, including truncated tail and enlarged heart [41].…”
Section: Temporal Expression Of Gonadotropins In Zebrafishsupporting
confidence: 93%
“…The expression of GtH mRNA was more efficiently suppressed by GtHα RNAi expression compared with the other two subunits. They suggested that GtHα RNAi may be an essential factor in the further development of sterility technology of transgenic fish for biosafety purposes [76]. However, we discovered a new alternative splicing transcript of the GtH alpha subunit from the pituitary glands and ovaries of common carp.…”
Section: Reproductive Containment Strategies Of Transgenic Fishmentioning
confidence: 81%
“…Huang et al [76] reported using RNA interference (RNAi) to knockdown GtHα, FSHβ and LHβ genes. The RNA or protein expression levels of the GtH genes were monitored by RT-PCR, Southern blotting, and GFP analyses.…”
Section: Reproductive Containment Strategies Of Transgenic Fishmentioning
confidence: 99%
“…Data obtained in this study would also be a useful basis for future application of living fluorescence color reporters to genomic and transgenic researches with this species. Also the transgenic O. dancena lines to stably express the fluorescent reporter in whole body throughout entire lifespan might serve as a fundamental platform to facilitate the set-up and/or designation of the developmental stage-or tissue-specific RNA interference experiments (see Xie et al 2005;Huang et al 2008). …”
Section: Regulation Of Rfp Transgene At Transcription Level In Transgmentioning
confidence: 99%